UV tackifying pressure-sensitive adhesive, support film and preparation method of UV tackifying pressure-sensitive adhesive

By introducing UV light fracture crosslinking agent into UV sticking type pressure sensitive adhesive, the problem of poor pasting during the bonding of the support film is solved, the reworkability and permanent bonding effect of the support film are achieved, and the OLED screen body is improved fit quality and yield rate.

CN119242224APending Publication Date: 2025-01-03SUZHOU SHIHUA NEW MATERIAL TECH

Patent Information

Application Number
CN202411421029.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

When applying to the OLED screen, the existing support film is prone to poor adhesion such as bubble mixing, sticking position offset, etc. When applying to the OLED screen, the high adhesion force makes it difficult to peel off and cannot be reworked and re-fitted, resulting in low yield and waste of raw materials.

Method used

UV tackifying pressure-sensitive adhesive is used to reduce the crosslinking degree and increase adhesion by introducing the fracture reaction of crosslinking agent under UV light irradiation; reduce the adhesion during initial bonding, facilitate removal, and pass through UV Curing improves adhesion and ensures a permanent fit.

Benefits of technology

The reworkability of the support film is achieved, the material waste is avoided when the bond is poor, and the permanent bonding effect is provided after confirming that the bonding is normal, which improves the bonding quality and yield of the OLED screen.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242224A_ABST
    Figure CN119242224A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of pressure-sensitive adhesives, in particular to a UV tackifying type pressure-sensitive adhesive, a supporting film and a preparation method of the UV tackifying type pressure-sensitive adhesive. A cross-linking agent with UV responsiveness is prepared, the cross-linking agent is compounded with a glue master batch to obtain a pressure-sensitive adhesive with a tackifying characteristic, the pressure-sensitive adhesive is coated on the surface of an optical-grade film according to a certain thickness, and a release film and a protective film are covered on the surface of the optical-grade film. Under the irradiation of UV light, a light-sensitive chemical structure in molecules of the cross-linking agent is broken, so that the cross-linking degree of the pressure-sensitive adhesive is reduced, then active groups providing adhesion characteristics in masterbatch are exposed on an adhesion interface, the adhesion of the support film is increased, the support film has relatively small viscosity during initial lamination, and the adhesion performance of the support film is improved. And the material waste caused by incapability of reworking and re-laminating under the poor sticking conditions such as bubble mixing and sticking position deviation in the laminating process is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pressure-sensitive adhesives, in particular to a UV tackifying pressure-sensitive adhesive, a support film and a preparation method thereof. Background Art

[0002] Back Plate Film is an optical film material used in the flexible OLED process. After being attached to the OLED panel, it can play a role in reinforcement and support, preventing the panel from tearing or curling during application.

[0003] For example, the Chinese patent with publication number CN110862782A discloses a protective film tape for flexible OLED support, which comprises, from top to bottom, a first substrate layer, an antistatic acrylic pressure-sensitive adhesive protective layer, an antistatic polyacrylic resin hardening layer, a second substrate layer, a special polyacrylic adhesive layer and a PET double-sided antistatic release film layer.

[0004] The tape has excellent bonding effect and can effectively prevent the risk of OLED devices heating up during use or device damage due to insufficient adhesiveness of the tape during thermal disassembly of the mobile phone screen; at the same time, it ensures that the tape has excellent anti-static effect when in use.

[0005] However, including the above patents, conventional support films need to provide permanent support after lamination and cannot be significantly displaced, so the pressure-sensitive adhesive used in the film material has a relatively high adhesive force. In the process of laminating the support film to the screen body, there are cases of poor lamination such as air bubbles mixed in and lamination position deviation. The support film with high adhesive force is difficult to peel off and cannot be reworked and re-laminated, resulting in problems such as low yield rate and waste of raw materials.

[0006] In order to solve the above problems, the present invention provides a UV tackifying pressure-sensitive adhesive, a supporting film and a preparation method thereof. Summary of the invention

[0007] The object of the present invention is to provide a UV tackifying pressure-sensitive adhesive, a supporting film and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0009] A method for preparing a UV tackifying pressure-sensitive adhesive, comprising the following substances by weight:

[0010] Acrylic polymer 100 parts

[0011] UV breaking curing agent 0.5-2 parts

[0012] Other additives 0.5-1 part;

[0013] The acrylic polymer comprises butyl acrylate, acrylic acid, an initiator and a solvent.

[0014] More optimally, when preparing the acrylic polymer, 95 parts of butyl acrylate, 5 parts of acrylic acid, 0.2 parts of initiator, and 200 parts of solvent are taken and reacted at 60 degrees for 8 hours to obtain the acrylic polymer.

[0015] More preferably, the molecular weight of the acrylic acid polymer is 600,000.

[0016] More optimally, the initiator is azobisisobutyronitrile; the solvent is ethyl acetate.

[0017] More optimally, the UV breaking curing agent is a homemade epoxy curing agent with a purity of 96.7%.

[0018] More optimally, the preparation of UV breaking curing agent includes the following steps:

[0019] S1, take 5 g of 2-nitroterephthalic acid, add it to 100 mL of borane-tetrahydrofuran complex solution, stir at room temperature for 4 hours, and then reflux and stir at 50°C for 15 hours;

[0020] S2, add 2.2 g of 3-butenoic acid and stir at room temperature for 5 hours; finally, add 3.6 g of 3-chloroperoxybenzoic acid and stir at room temperature for 24 hours;

[0021] S3, obtaining a finished product of UV breaking type curing agent after separation and purification;

[0022] The concentration of the borane-tetrahydrofuran complex solution was 2 mg / mL.

[0023] More preferably, other additives include silane coupling agents and leveling agents.

[0024] More optimally, the content ratio of the silane coupling agent to the leveling agent is 5:1.

[0025] The invention provides a UV tackifying pressure-sensitive adhesive, which is prepared by using any one of the above-mentioned preparation methods of the UV tackifying pressure-sensitive adhesive.

[0026] The present invention also provides a UV tackifying support film, which is made of the above-mentioned UV tackifying pressure-sensitive adhesive and comprises a protective film layer, a PET layer, a UV tackifying adhesive layer and a release film layer which are arranged in sequence.

[0027] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0028] (1) In the present invention, a UV-responsive crosslinking agent is prepared, and after compounding with a glue masterbatch, a pressure-sensitive adhesive with tackifying properties is obtained, which is coated on the surface of an optical-grade film at a certain thickness, and covered with a release film and a protective film. Under UV light irradiation, the light-sensitive chemical structure in the crosslinking agent molecule will break, causing the crosslinking degree of the pressure-sensitive adhesive to decrease, and then the active groups in the masterbatch that provide adhesion properties are exposed on the adhesion interface, resulting in increased adhesion of the support film.

[0029] (2) In the present invention, the crosslinking agent in the pressure-sensitive adhesive formula is specially designed to introduce a chemical structure that can be broken by UV light, and the UV viscosity-enhancing effect is achieved by changing the crosslinking density of the system before and after UV light irradiation.

[0030] (3) In the present invention, on the one hand, there is no need to introduce other masterbatch components such as oligomers and tackifying resins, thereby ensuring the purity of the system and the stability of the formula; on the other hand, only the cross-linking agent component is changed, which will not have a significant impact on the performance of the acrylic master glue, and can be applied to a variety of different types of acrylic glues according to specific application requirements.

[0031] (4) In the present invention, after the curing agent is added, the difunctional epoxy group can undergo a cross-linking reaction with the carboxyl group and other groups in the acrylic glue to cure the glue, shield the polar groups such as the carboxyl group, and reduce the peeling force; when irradiated with UV light, the o-nitrobenzyl ester group in the curing agent decomposes and rearranges under the ultraviolet light, breaks, and generates o-nitrobenzaldehyde and carboxylic acid, so that the curing degree of the glue is reduced, more polar groups are exposed, and the peeling force is increased.

[0032] (5) In the present invention, a reworkable support film is prepared, so that the support film has a low adhesive force in the initial stage of bonding, and is easy to remove after poor bonding occurs, ensuring that no foreign matter remains on the screen; after confirming that the bonding is normal, the adhesion of the support film is improved by ultraviolet light (UV) curing, so that it is firmly bonded to the OLED screen, providing permanent bonding and support for the screen. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0034] Figure 1 It is a schematic diagram of the structure of the UV adhesion-enhancing support film;

[0035] Figure 2 This is the synthesis route diagram of UV breaking type curing agent.

[0036] In the figure, 1, protective film layer; 2, PET layer; 3, UV adhesion enhancing adhesive layer; 4, release film layer. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The present invention provides a UV tackifying pressure-sensitive adhesive, a support film and a preparation method thereof, which are used to solve the problems of poor pasting such as air bubbles mixed in and pasting position deviation in the process of pasting the support film to the screen body, and the high-adhesive support film is difficult to peel off and cannot be reworked and re-pasted, resulting in low yield rate and waste of raw materials. Figure 1 As shown, the prepared UV tackifying support film includes a protective film layer, a PET layer, a UV tackifying adhesive layer and a release film layer which are arranged in sequence.

[0039] The invention provides a method for preparing a UV tackifying pressure-sensitive adhesive. The method comprises, by weight, 100 parts of an acrylic polymer, 0.5-2 parts of a UV breaking curing agent, and 0.5-1 parts of other additives. The synthetic formula of the acrylic polymer is 95 parts of butyl acrylate, 5 parts of acrylic acid, 0.2 parts of an initiator azobisisobutyronitrile, and 200 parts of a solvent ethyl acetate. The reaction is carried out at 60 degrees for 8 hours to obtain an acrylic polymer with a molecular weight of 600,000. The UV breaking curing agent is synthesized by itself and is an epoxy curing agent with a purity of 96.7%. The other additives include a silane coupling agent and a leveling agent.

[0040] When preparing the UV breaking curing agent, the following steps are included: take 5g of 2-nitroterephthalic acid, add it to 100mL of borane-tetrahydrofuran complex solution (2mg / mL), stir at room temperature for 4 hours, and then reflux and stir at 50°C for 15 hours; then add 2.2g of 3-butenoic acid, stir at room temperature for 5 hours; finally add 3.6g of 3-chloroperoxybenzoic acid, stir at room temperature for 24 hours; and obtain the product after separation and purification. The specific synthesis route is as follows Figure 2 shown.

[0041] In order to verify the performance effect of the prepared support film, the present invention provides several embodiments and comparative examples, and conducts a 180° peeling force test.

[0042] Performance test conditions and methods:

[0043] The following tests were conducted at room temperature 23°C ~ 50% RH under yellow light conditions.

[0044] 180° peeling force test before UV:

[0045] Lay the adhesive surface of the sample onto a stainless steel mirror steel plate (length 150mm×width 50mm×thickness 2mm and surface roughness: 10nm±10nm) that meets the material requirements of the peeling test steel plate of GB / T2792. Pay attention to the smooth lamination without bubbles, impurities, wrinkles, etc.

[0046] Use a 2kg roller to roll the sample back and forth on the stainless steel mirror steel plate with the sample at a speed of 300mm / min once, let it stand for 20 minutes under the test environment (23℃~50%RH), and then use a tensile machine to perform a 180° peel strength test under the test environment (23℃~50%RH) after standing. The peeling speed is 300mm / min, the number of test samples is 3, and the arithmetic mean of the 3 test results is taken as the peeling force result.

[0047] 180° peeling force test after UV:

[0048] Lay the adhesive surface of the sample onto a stainless steel mirror steel plate (length 150mm×width 50mm×thickness 2mm and surface roughness: 10nm±10nm) that meets the material requirements of the peeling test steel plate of GB / T2792. Pay attention to the smooth lamination without bubbles, impurities, wrinkles, etc.

[0049] Use a 2kg roller to roll the sample back and forth on the stainless steel mirror steel plate with the sample strip at a speed of 300mm / min. After standing for 20 minutes in the test environment (23℃~50%RH), place it vertically in a UV light box and irradiate it with ultraviolet light of 365nm wavelength, perpendicular to the direction of sample strip bonding, for 30 seconds. The irradiation ultraviolet light energy is>600mJ / cm 2 ;

[0050] After irradiation, a 180° peel strength test was performed using a stretching machine under a test environment (23°C ~ 50% RH), the peel speed was 300 mm / min, the number of test samples was 3, and the arithmetic mean of the 3 test results was taken as the peel strength result.

[0051] In the embodiment of the present invention, an acrylic polymer, a homemade UV-breaking epoxy curing agent and an additive (silane coupling agent / leveling agent = 5:1) are used; in the comparative example, an acrylic polymer, a traditional epoxy curing agent and an additive (silane coupling agent / leveling agent = 5:1) are used. The composition and performance test parameters of the specific embodiment and comparative example are shown in Table 1.

[0052] Table 1 Composition and performance parameters of various embodiments and comparative examples

[0053]

[0054]

[0055] According to the data analysis in Table 1, compared with Comparative Examples 1 and 2, after using the UV-breaking epoxy curing agent, the peeling force of the support film on the adhered glass is significantly increased after UV light irradiation in Examples 1-4. This is because the molecular structure of the curing agent of the pressure-sensitive adhesive used in the examples is broken after UV light irradiation, resulting in a decrease in the cross-linking degree of the glue, a weakening of the cohesive force, and exposure of the active groups, thereby enhancing the adhesion and improving the peeling force.

[0056] Therefore, it can be ensured that the support film prepared by the present invention has less viscosity during the initial bonding, thereby avoiding the waste of materials caused by the inability to rework and re-bond due to poor bonding such as air bubbles mixed in and the bonding position shifting during the bonding process.

[0057] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0058] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a UV tackifying pressure-sensitive adhesive, characterized in that: The components by weight include the following substances: Acrylic polymer 100 parts UV breaking curing agent 0.5-2 parts Other additives 0.5-1 part; The acrylic polymer comprises butyl acrylate, acrylic acid, an initiator and a solvent.

2. The method for preparing a UV tackifying pressure-sensitive adhesive according to claim 1, characterized in that: When preparing the acrylic polymer, 95 parts of butyl acrylate, 5 parts of acrylic acid, 0.2 parts of initiator and 200 parts of solvent are taken and reacted at 60 degrees for 8 hours to obtain the acrylic polymer.

3. The method for preparing a UV tackifying pressure-sensitive adhesive according to claim 2, characterized in that: The molecular weight of the acrylic polymer is 600,000.

4. The method for preparing a UV tackifying pressure-sensitive adhesive according to claim 2, characterized in that: The initiator is azobisisobutyronitrile; and the solvent is ethyl acetate.

5. The method for preparing a UV tackifying pressure-sensitive adhesive according to claim 1, characterized in that: The UV breaking curing agent is a homemade epoxy curing agent with a purity of 96.7%.

6. The method for preparing a UV tackifying pressure-sensitive adhesive according to claim 5, characterized in that: The preparation of the UV breaking type curing agent comprises the following steps: S1, take 5 g of 2-nitroterephthalic acid, add it to 100 mL of borane-tetrahydrofuran complex solution, stir at room temperature for 4 hours, and then reflux and stir at 50°C for 15 hours; S2, add 2.2 g of 3-butenoic acid and stir at room temperature for 5 hours; finally, add 3.6 g of 3-chloroperoxybenzoic acid and stir at room temperature for 24 hours; S3, obtaining a finished product of UV breaking type curing agent after separation and purification; The concentration of the borane-tetrahydrofuran complex solution is 2 mg / mL.

7. The method for preparing a UV tackifying pressure-sensitive adhesive according to claim 1, characterized in that: The other additives include silane coupling agents and leveling agents.

8. The method for preparing a UV tackifying pressure-sensitive adhesive according to claim 7, characterized in that: The content ratio of the silane coupling agent to the leveling agent is 5:

1.

9. A UV tackifying pressure-sensitive adhesive, characterized in that: The method is prepared by using any one of the preparation methods of UV tackifying pressure-sensitive adhesives as described in claims 1 to 8.

10. A UV tackifying support film, made using the UV tackifying pressure-sensitive adhesive according to claim 9, characterized in that: It comprises a protective film layer, a PET layer, a UV adhesion enhancing adhesive layer and a release film layer which are arranged in sequence.

Citation Information

Patent Citations

  • Pressure-sensitive adhesive capable of realizing visbreaking through both UV irradiation and heating manners, and preparation method thereof

    CN110358471A

  • UV tackifying glue and preparation method thereof

    CN116218423A

  • Acrylic acid pressure-sensitive adhesive with UV tackifying and heating visbreaking functions as well as preparation method and application of acrylic acid pressure-sensitive adhesive

    CN118185520A

  • UV tackifying adhesive tape and preparation method thereof

    CN118546632A

Cited By

  • Optical support film capable of being tackified by ultraviolet (UV)

    CN121610206A